Pengaruh Artificial Intelligence dan Digital Marketing terhadap Minat Beli Konsumen - Franycia Maria Pangkey; Lalu M Furkan; Lalu Edy Herman Mulyono (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
The purpose of this paper is to investigating the influence of Artificial Intelligence and Digital Marketing to Consumers Buying Intention. Artificial Intelligence development revolutionize digital marketing as well as customer buying intention and thus boost sales. Artificial Intelligence and Digital Marketing in combination with rapidly developing technologies kind of tracking, buying, cashless. Everything goes to simple touch, will bring opportunities to consumers to having a practical best service. This paper uses quantitative approach that rooted in the Artificial Intelligence, Digital Marketing and Customer Buying Intention Literature, that was carried out using structural equation modeling (SEM) based on partial least square (PLS), with 74 respondents. The contribution of this paper examines consumer perseption, beliefs and behaviours of buying intention of online transportation (gojek) in millenials based on artificial intellegence and digital marketing developing. And a result of this study, artificial intelligence and digital marketing have positively effects to Consumer Buying Intention.In this present research  helps service organizations and their management better implications of keep up with the developments of service. This paper talks about artificial intelligence and digital marketing based on consumer buying intention Keywords – Consumer Buying Intentions, Artificial Intelligence, Digital Marketing, Online Transportation,